Orang Tua sebagai Pendidik Kristen terhadap Peningkatan Kognitif Anak Umur 6-15 Tahun - Nice Zega; Murnihati Gulo; Hadirman Gulo; Erinida Gulo (Jurnal Teologi Pambelum, 2026)
Parents are assigned by God to be the primary educators of their children. A Christian educator certainly wants to increase their children's knowledge about God and others. The good or bad of a child's knowledge depends on the role of parents in educating children at home. The purpose of this study is to determine the role of parents as Christian educators in increasing the knowledge of children aged between 6-15 years in Salo'o Village, Ulu Moro'o District, West Nias Regency. The population in this study were parents in Salo'o Village, Ulu Moro'o District, West Nias Regency who have children aged 6-15 years totaling 30 families. The data obtained were analyzed using a frequency distribution percentage. The research method used is descriptive quantitative, to explain a phenomenon or condition without examining cause and effect by focusing on the nature of an event. From the results of the study, the author concludes that there is a significant role of parents as Christian educators in student learning motivation in the cognitive development of children aged 6-15 years in Salo'o Village, Ulu Moro'o District, West Nias Regency. The value of the role of parents as Christian educators is positive. This means that parents as Christian educators play a positive role in improving the cognitive abilities of children aged 6-15 years in Salo'o Village, Ulu Moro'o District, West Nias Regency. Furthermore, if the value of the role of parents as Christian educators is increased by one level, it will affect the cognitive abilities of children aged 6-15 years. Thus, there is an increase in children's cognitive abilities because there is a role of parents as Christian educators in the development of knowledge of children aged 6-15 years. This means that this study can be accepted where there is a positive and significant role of parents as Christian educators in improving the cognitive abilities of children aged 6-15 years in Salo'o Village, Ulu Moro'o District, West Nias Regency.